PENGARUH WAKTU PENGAPIAN TERHADAP KONSENTRASI EMISI TOTAL FORMALDEHIDA DARI MESIN SEPEDA MOTOR BERBAHAN BAKAR CAMPURAN BIOETANOL 10% DAN 20% - Rezki Tiara, Ledy
One sector that the largest contributor to air pollution is the transport sector that cause emissions from motor vehicles such as Hydrocarbon, Carbonmonoxide, Nitrogen oxide, etc. The use of bioethanol is one alternative effort that can be done to reduce emissions of harmful pollutants. However, the addition of bioethanol into fuel would increase the emission of formaldehyde and acetaldehyde gas. Formaldehyde is a colorless gas that has pungent odor, can irritate easily and soluble in water. In the air, formaldehyde concentration by 5 ppm or more potentially cause health problems. Therefore, observations of the concentration of formaldehyde emissions need to be done as an evaluation of the impact of the use of bioethanol. This study used active methods sampling known as 3-Methyl-2-Benzothiazolinone Hydrazone (MBTH) Colorimetric method. Principle of this method is formaldehyde from four steps motorcycle exhaust flowed into the modified Constant Volume Sampler (CVS) system then flowed into a tube containing MBTH solution. Formaldehyde will react with MBTH and stable after one hour. Furthermore, the solution is mixed with an oxidizing reagent for 12 minutes and produce green to bluish. Color intensity will be measured on a spectrophotometer with a wavelength of 630 nm. Measurements performed to analyze the relationship between formaldehyde concentrations with a bio-ethanol mixed fuel based on ignition timing. Ignition timing variation used is retard (5 ° -20 °), standard (10 ° -25 °), and advance (15 ° -30 °). While the variation of the fuel used is 10% and 20% bioethanol. This study found that the retarded ignition timing resulted a lower formaldehyde emissions than standard ignition timing, most likely caused by more complete combustion and thorough. While the ignition timing advanced yield higher formaldehyde emissions.